Emerging story of gut dysbiosis in spondyloarthropathy: From gastrointestinal inflammation to spondyloarthritis - Lyu, Xing; Chen, Jieli; Gao, Xingjie; Yang, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
As a set of inflammatory disorders, spondyloarthritis (SpA) exhibits distinct pathophysiological, clinical, radiological, and genetic characteristics. Due to the extra-articular features of this disorder, early recognition is crucial to limiting disability and improving outcomes. Gut dysbiosis has been linked to SpA development as evidence grows. A pathogenic SpA process is likely to occur when a mucosal immune system interacts with abnormal local microbiota, with subsequent joint involvement. It is largely unknown, however, how microbiota alterations predate the onset of SpA within the “gut-joint axis”. New microbiome therapies, such as probiotics, are used as an adjuvant therapy in the treatment of SpA, suggesting that the modulation of intestinal microbiota and/or intestinal barrier function may contribute to the prevention of SpA. In this review, we highlight the mechanisms of SpA by which the gut microbiota impacts gut inflammation and triggers the activation of immune responses. Additionally, we analyze the regulatory role of therapeutic SpA medication in the gut microbiota and the potential application of probiotics as adjunctive therapy for SpA.